Analisis Pendidikan Agama Kristen Terhadap Paham Radikalisme Dalam Konteks Indonesia - Doni A (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
This article offers an analysis of the role of Christian religious education in overcoming radicalism in the Indonesian context. Radicalism in Indonesia is multifaceted, and religious, political, social, and ethnic factors contribute to its prevalence. Religious differences often give rise to misunderstandings and violence which then occurs. Political radicalism stems from power dynamics, including state-sponsored oppression or interstate conflict. Social radicalism manifests through extreme tactics aimed at societal transformation, sometimes ignoring legal norms. Ethnic radicalism promotes a supremacist ideology, justifying violence or discrimination against other ethnic groups. Using qualitative research and literature analysis, this research explores the intersection between Christian education, radicalism, and diversity. The results of research on Christian religious education in Indonesia emphasize values such as diversity, tolerance and peace, which provide a counterweight to radical ideology. By prioritizing these values, Christian education fosters stability across religious, political, social and ethnic dimensions, thereby reducing the risks posed by radicalism. This research underlines the importance of Christian religious education in cultivating a society that is cohesive and tolerant of radical influences.